Utilisation of an in vivo malaria model to provide functional proof for RhopH1/CLAG essentiality and conserved orthology with P. falciparum - Mitchell L. Trickey; Mrittika Chowdury; Georgina Bramwell; Natalie A. Counihan; Tania F. de Koning-Ward (Journal of Biomedical Science)
Abstract Background Malaria parasites establish new permeation pathways (NPPs) at the red blood cell membrane to facilitate the transport of essential nutrients from the blood plasma into the infected host cell. The NPPs are critical to parasite survival and, therefore, in the pursuit of novel therapeutics are an attractive drug target. The NPPs of the human parasite, P. falciparum, have been linked to the RhopH complex, with the monoallelic paralogues clag3.1 and clag3.2 encoding the protein RhopH1/CLAG3 that likely forms the NPP channel-forming component. Yet curiously, the combined knockout of both clag3 genes does not completely eliminate NPP function. The essentiality of the clag3 genes is, however, complicated by three additional clag paralogs (clag2, clag8 and clag9) in P. falciparum that could also be contributing to NPP formation. Methods Here, the rodent malaria species, P. berghei, was utilised to investigate clag essentiality since it contains only two clag genes, clagX and clag9. Allelic replacement of the regions encompassing the functional components of P. berghei clagX with either P. berghei clag9 or P. falciparum clag3.1 examined the relationship between the two P. berghei clag genes as well as functional orthology across the two species. An inducible P. berghei clagX knockout was created to examine the essentiality of the clag3 ortholog to both survival and NPP functionality. Results It was revealed P. berghei CLAGX and CLAG9, which belong to two distinct phylogenetic clades, have separate non-complementary functions, and that clagX is the functional orthologue of P. falciparum clag3. The inducible clagX knockout in conjunction with a guanidinium chloride induced-haemolysis assay to assess NPP function provided the first evidence of CLAG essentiality to Plasmodium survival and NPP function in an in vivo model of infection. Conclusions This work provides valuable insight regarding the essentiality of the RhopH1 clag genes to the NPPs functionality and validates the continued investigation of the RhopH complex as a therapeutic target to treat malaria infections.